Analisis Efektivitas Strategi Pemasaran Kontroversial Pada Brand Porteegoods - Novianti, Reva; Sukoco, Iwan; Barkah, Cecep Safa’atul; Novel, Nurillah Jamil Achmawati (Bina Nusantara University, 2024)
In the digital era, social media demonstrates significant potential as a platform for digital marketing. However, consumers are becoming increasingly critical of marketing content, challenging businesses to create innovative and engaging content. In the competitive fashion industry, controversial marketing strategies have emerged as a way to attract consumer attention. Porteegoods, a local shoe brand, has built a reputation for unique and controversial marketing. Porteegoods faces allegations of design plagiarism, coupled with a unique and provocative marketing strategy on social media. This research employs a descriptive qualitative method supported by library research and basic observations from social media to describe the effectiveness of Porteegoods' marketing communication. The aim of this research is to analyze the effectiveness of Porteegoods' controversial marketing strategy on social media. The results of this study indicate that the controversial marketing communication strategy implemented by Porteegoods can be considered effective in attracting attention, building brand awareness, and even increasing sales for Porteegoods. However, the communication process is still considered less effective due to the presence of noise